Bentuk Perlindungan Hukum Terhadap Nasabah Bank Pengguna Layanan Internet Banking Menurut Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Mohammad Dluha; Yusi Ira Ariska (JUSTNESS - Jurnal Hukun dan Agama, 2021)
Internet Banking services in addition to providing convenience but also providing risks, there are various modes of fraud by utilizing the Internet and system failures, so that legal protection for customers can not be guaranteed, the rights and obligations of customers tend to be unclear which in turn results in problems arising from internet banking transactions. cannot be resolved properly, even sexing customers are on the disadvantaged side.So this study aims to find out how the legal protection and liability provided by the bank to customers using internet banking services in terms of Law No. 8 of 1999 concerning Consumer Protection.By using a normative juridical research method, the problem approach used is the law approach and uses secondary legal materials.The results obtained from this study are that although there are no laws and regulations that specifically regulate internet banking, in a positive legal order in Indonesia there are laws and regulations that can provide legal protection for customers who use Internet banking services, namely the Act. Law Number 8 of 1999 concerning Consumer Protection. The implementation of customer protection for internet banking service users starts from the aspect of transparency of internet banking product information, the security aspect of internet banking technology, and the aspect of the bank's responsibility for losses. However, if the bank acts against the law, the customer can file a lawsuit to the district court by proving that the bank has committed an unlawful act as stated in article 1365 of the Civil Code.. Keyword: Law number 8 of 1999 concerning Consumer Protection, Internet Banking, Internet Banking Users